Biological and therapeutic effects of honey produced by honey bees and stingless bees: a comparative review - Rao,Pasupuleti Visweswara (2016)
ABSTRACT Honey is a natural product produced by both honey bees and stingless bees. Both types of honey contain unique and distinct types of phenolic and flavonoid compounds of variable biological and clinical importance. Honey is one of the most effective natural products used for wound healing. In this review, the traditional uses and clinical applications of both honey bee and stingless bee honey – such as antimicrobial, antioxidant, anti-inflammatory, anticancer, antihyperlipidemic, and cardioprotective properties; the treatment of eye disorders, gastrointestinal tract diseases, neurological disorders, and fertility disorders and wound healing activity are described.